UPAYA PENINGKATAN KUALITAS CRUDE PALM OIL (CPO) DENGAN SIKLUS PDCA (PLAN, DO, CHECK, ACTION) DI PT. SUMBER SAWIT SEJAHTERA PKS TERANTANG MANUK - Wresni Anggraini; Sutikno Sutikno (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2011)
Crude Palm Oil (CPO) is an agribusiness commodities that has strategic value. Competition palm oil export with Malaysian makes the Indonesian CPO products must have international standard quality.. The high content of FFA decrease of CPO quality. The objective of this research are determining  the factors that cause the increasing of FFA levels (Free Fatty Acid) by using  fishbone diagram and decide the improvements for the company in order to improve quality of CPO (Crude Oil Palm). This research discusses about the efforts to improve  quality of CPO by implementation PDCA cycle at PT. Sumber Sawit Sejahtera PKS Terantang Manuk. Based on the data analysis, the dominant factor causing high content of FFA is coming from  reception station TBS. By using a fishbone diagram, it was known that the reasons for high FFA content because of less skilled workers, and the  workers  do their work carelessly, weak fruit sorting, high of restant fruit, TBS cuts, TBS rotten, brondolan crushed the truck, using heavy equipment, and sorting of TBS outdoor. Quality Improvement could be done by  implementation of briefing, the proposed place of rest, improved sorting supervision, schedule of TBS supply, reduce the use of heavy equipment, supervision of FIFO system, and clean the floor sorting of brondolan. With the implementation of continuous improvement efforts makes the content of FFA CPO  decreased an average content of FFA before the improvements is 3.26% and after the improvement  average of  FFA levels 2.75% . FFA above 3.00%  decreased by 68.00%.  Keywords             : crude, palm, oil, fishbone, diagram, improvement, quality.